The Clinical Outcomes of Primary Angioplasty in Hospitalized Patients with ST-Segment Elevation Acute Myocardial Infarction Were Investigated at Imam Reza Hospital from 1399 to 1401 - Omid Khosravi; Mohammad Mahdi Shekarian Yazd (Journal of Cardio-Thoracic Medicine)
Introduction: Ischemic heart disease (IHD) is a major global health concern with significant implications for patient mortality and life expectancy. Effective management of IHD heavily relies on vascular reconstruction procedures, including percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG).Material and Method: This study was conducted at Imam Reza Hospital, evaluating 103 patients with myocardial infarction with ST elevation (MI-STE) who underwent PCI. The cohort comprised 84 men and 19 women across varying age ranges. A subset of these patients had a history of CABG, addiction, or a family history of heart disease. The study focused on the types of stents used, with Supraflex and Xience being the most common, primarily in lengths of ≤20 mm and diameters of 2.75 mm. Post-PCI complications were also assessed, including hematoma at the angiography site, rehospitalization, coronary artery revascularization, contrast-induced nephropathy (CIN), no reflow, in-stent restenosis (ISR), coronary artery dissection, and cardiogenic shock.Result and Conclusion: The overall population experienced a low mortality rate of 1.9%. Notably, cardiogenic shock was significantly associated with mortality, posing a 100-fold increased risk. This study underscores the importance of monitoring and managing post-PCI complications to improve patient outcomes and reduce mortality in individuals with IHD. Further research is warranted to explore preventive strategies and optimize treatment approaches for this patient population.